#TITLE_ALTERNATIVE# - INDRA PRASETYA ( NIM 12908003 ), ADHI
The calculation of Net Primary Productivity (NPP) to determine the fertility of Java Sea was conducted using Carbon-based Production Model(CbPM). The input data that was used to calculate are monthly data from January 2002 to July 2013 of surface chlorophyll concentration (Chl), particulate backscattering coefficients (Bbp), coefficient diffusion attenuation with the wavelength 490nm (K490), and photosynthetically active radiation (PAR) that is obtained fromAqua-MODIS satellite, and mixed layer depth (MLD).Calculation result for mean NPP seasonal from 2002-2013 in Java Sea shows range of 680-2800 mgCm-2 per day. NPP during west monsoon range in 700-2600 mgCm-2 per day, transitional season 1 range in 700-2800 mgCm-2 per day, east monsoon range in 750-2600 mgCm-2/day, and transitional season 2 range in 680-2560 mgCm-2/day. Calculation result of the correlation coefficient between monthly NPP anomalies in the Java Sea with Australian Monsoon Index and the Southern Oscillation Index shows that variation of the NPP inJava Sea is more influenced by the monsoon rather than the El Nino SouthernOscillation (ENSO).